Comparative Accuracy of Automated Upper Arm and Wrist Blood Pressure Devices: A Comparison with Intra-arterial line - Ahmed Abdulwahid (مجلة الكوفة الطبية)
Background: Accurate measurement of blood pressure is crucial for the diagnosis and treatment of the cardiovascular system diseases. Automatic non-invasive blood pressure devices are now widely for the measurement of blood pressure patients at home and even by the doctors in emergency room in Iraq due to their ease of use. However, the accuracy of these devices had been a matter of debate. Aim of the study: Our study aimed to evaluate the accuracy of the automated wrist and upper arm devices in blood pressure measurement. Methods: The study was a cross sectional study involved 75 patients who were undergoing cardiac catheterization. Blood pressure was measured using two types of automated devices, Rossmax upper arm and wrist devices. Their readings were compared simultaneously with the readings of an intra-arterial catheter to assess their accuracy. Results: The automated upper arm and wrist devices measured a higher value of systolic, diastolic and mean arterial pressures than those measured by intra-arterial catheter with mean of differences of 6.11 mmHg, 6.79 mmHg and 6.57 mmHg respectively, regarding the upper arm device. The mean of differences of the readings of systolic, diastolic and mean arterial blood pressures measured by wrist device were 11.32 mmHg, 18.30 mmHg and 15.98 mmHg, respectively. Both devices exhibited good reproducibility. Conclusion: Rossmax upper arm and wrist devices overestimate blood pressure. They are inaccurate and should not be relied upon for critically ill patients and in the emergency room.